INFLUENCE OF DEMOGRAPHIC FACTORS ON ENTREPRENEURIAL SUCCESS IN KENYA - Karogo, Mercy Gathigia; Nyaboga, Andrew; Marwa, Mwita; Waiguchu, Muruku (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: The purpose of this research was to assess the influence of age, education and business experience on entrepreneur success in Kenya. Methodology: The study applied a descriptive research design. The researcher used both structured questionnaire that was designed for the entrepreneurs and interview schedules that were designed for SME managers/owners. The analysis of data was done using the Statistical Package for Social Sciences (SPSS version 23.0) computer software. Results: The findings indicate that the age and education level of entrepreneurs influence their success while the influence of their experience before the start of business contributes little to their success. Unique Contribution to Theory, Policy and Practice: The study recommended the revision of Kenya's educational curriculum to incorporate entrepreneurship skills at all levels of education.